Dampak Obsessive Love Disorder dan Upaya Penyadarannya Bagi Remaja - Isak (Sekolah Tinggi Teologi Ekumene Jakarta., 2025)
Adolescence is a crucial phase for identity formation and the development of social relationships. However, not all relationships established by adolescents are healthy. One increasingly common phenomenon is Obsessive Love Disorder (OLD), a psychological condition in which an individual becomes excessively obsessed with another person, often leading to possessive and controlling behavior. This disorder negatively impacts adolescents’ emotional and social development. This study aims to examine the effects of OLD on adolescents and to propose effective awareness strategies. A qualitative descriptive approach was employed through a literature review. The findings suggest that raising awareness about the dangers of OLD should not rely solely on conventional methods such as seminars, but must also utilize social media platforms. In particular, educational videos are a relevant and engaging medium for the digital generation. Creative and contextual education is expected to help adolescents build healthy, non-obsessive relationships.